Phytoremediation study: factors influencing heavy metal uptake of plants - Máthé-Gáspár, Gabriella; Anton, Attila (Acta Biologica Szegediensis, 2005)
Factors influencing heavy metal uptake of plants were studied by pot and field experiments. All results concern soils and dump samples originated from the surrounding of Pb/Zn mine at Gyöngyösoroszi characterised with high complex heavy metal content. This summarising work demonstrated effects on the heavy metal content of 20 cultivated and wild plant species, being determined with a view to phytoremediation. Influences of the most important plant species (developmental stage, plant parts, and ecological factors, such as pH-value, temperature, soil treatment with lime and lignite) were examined. Interaction between ecological factors and plant characters was demonstrated, as well as results of pot and field studies were compared. Tested plant species were grouped on the basis of their accumulation capability and susceptibility of heavy metals.